Core-sheath structural carbon materials for integrated enhancement of thermal conductivity and capacity. (1st May 2018) - Li, Ang; Wang, Jingjing; Dong, Cheng; Dong, Wenjun; Atinafu, Dimberu G.; Chen, Xiao; Gao, Hongyi; Wang, Ge
Highlights: Core-sheath CNT@PC with 3D network structure was synthesized. The carbon sheath was conductive to the stability of network structure. The CNTs provide heat transfer paths for ss-PCMs. The hierarchical porous carbon sheath reduced interfacial thermal resistance. The ss-PCMs exhibited excellent thermal storage capability (up to 99.9%). Abstract: Energy storage capacity and heat transfer ability are two important indexes for shape-stabilized phase change materials (ss-PCMs). In this paper, a core-sheath CNT@PC was prepared via carbonation of CNT@ZIF-8, simultaneously 3D structural supports were obtained due to the porous carbon (PC) sheath stabilized the CNT@PC network structure. Porous carbon (PC), derived from carbonized metal organic frameworks (MOFs), exhibited high porosity and large specific surface area. PCMs, absorbed by capillary force of porous structure, was stabilized in the pores of PC sheath. Further, the interaction between PCMs and CNTs reduced the interfacial thermal resistance greatly. Carbon nanotubes (CNTs), acting as heat transfer pathways, provided continuous channels for phonons transfer and realized rapid heat transformation between ss-PCMs and external environment. The obtained SA/CNT@PC ss-PCMs exhibited excellent thermal conductivity (1.023 W/mK), large phase change enthepy (155.7 J g −1 ) and high thermal storage capabilities (99.9%). The thermal conductivity of SA/CNT@PC was improved 222.6% and phase change enthalpy was increased 92.6% over SA/PC ss-PCM. SA/CNT@PC with large energy storage density, flexible designation, simple operation and near-constant temperature properties during phase change process shows great potential in waste heat utilization.